The effect of socio economic status on students’ achievement in STEM-based learning - Nur Suhaidah Sukor; Mohd Zaki Ishak (Scholar Touch Publishers, 2018)
This paper discusses the impact of family income on students’ achievement in STEM-based learning. In this study a total of 129 students Form one (year 13) becomes sample of the research. The data was collected and analyzed by descriptive and two ways ANOVA. The science test contains 37 multiple choice items and reliability of Cronbach Alpha is 0.64. The findings show that there is significant effect on the group based variables on the mean score of the Science Test. There is also significant effect on the SES based variables on the mean score of Science Test. To encourage the participation of students from Middle Income and Lower Income families, the materials and tools used in module were inexpensive and easy-to-find. The findings also show that there is no significant interaction effect between the group-based variables and SES on the mean score of the Science Test. Implications of this research for teachers is to motivate them to employing STEM Inspiration Module in integrated STEM science classroom.